1995
DOI: 10.1103/physrevlett.75.584
|View full text |Cite
|
Sign up to set email alerts
|

Mustre de Leonet al.Reply:

Abstract: Mustre de Leon et al. Reply: Koval et al. [1] appear to agree with the physical results obtained in Ref. [2], but assert that our exact results for the coupled electron-phonon model can also be calculated accurately in an adiabatic approximation.We partially agree with this conclusion for some properties, but note that it can be reached only by comparison with a (numerically) exact calculation. In addition, we show that while an adiabatic approximation explains several of the exact results, it fails for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 4 publications
10
66
0
Order By: Relevance
“…According to various experimental data ͑x-rays and Raman spectroscopy, transport data, see, e.g., Ref. 18 and recent ion-channeling measurements 19 ͒, the apical oxygen position has two close minima, and this leads to the IE described by Eq. ͑8͒.…”
Section: Discussionmentioning
confidence: 99%
“…According to various experimental data ͑x-rays and Raman spectroscopy, transport data, see, e.g., Ref. 18 and recent ion-channeling measurements 19 ͒, the apical oxygen position has two close minima, and this leads to the IE described by Eq. ͑8͒.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is given by manganites [(La,Ca)MnO 3 ] [7] where the charge transfer occurs between Manganese atoms via an oxygen ion located between them. Several experiments [8,9] as well as theoretical studies [10] have established that in both above-mentioned systems oxygen and copper ions display a non-adiabatic behaviour. This affects the charge transfer between the reservoir and the conducting layer, because the latter process involves the motion of the non-adiabatic ions.…”
Section: Non-adiabatic Isotope Effectmentioning
confidence: 99%
“…A dynamic model that would lead to either a broadening or a split O͑4͒ position is the hopping small-polaron model, with the polaron hopping on and off the Cu-O͑4͒ bonds as discussed by Mustre de Leon et al 6 Ranninger 13 has calculated the XAFS signatures for the presence of polarons and shown that as the hopping speed decreases, the pairdistribution function first broadens and then splits; less than a factor of 2 in hopping speed is required to change from a broadened peak to a split peak. This is expected from the following simple argument.…”
Section: A Split O"4… Sitementioning
confidence: 99%
“…13 Å͒ in YBCO that decreases somewhat or disappears (␦rՇ0.11 Å͒ near T c . 5,6 Both of these measurements were initially treated with a fair amount of skepticism, because obtaining a reliable signal for measuring such small changes is difficult. The result of Horn et al has since been confirmed both by diffraction 7 and by capacitive dilatometry measurements 8 and consequently must be considered real, although its relation to T c is still unclear.…”
Section: Introductionmentioning
confidence: 99%